A Review Of Learning Management System Enhanced by Gamification Through Push Pool Mooring Model - Eddy Triswanto Setyoadi; Syaad Patmanthara; Heru Wahyu Herwanto; Hartarto Junaedi; Titasari Rahmawati (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2025)
The COVID-19 pandemic has led to the rapid expansion of online learning programs in higher education, enabling students to access and study course materials independently. The Learning Management System (LMS) is pivotal in supporting this transition. Incorporating gamification elements such as leaderboards, levels, point systems, and badges into LMS platforms can yield mixed effects on learning outcomes. While gamification has shown potential to enhance motivation, and engagement, and create a competitive yet enjoyable learning environment, it can also result in increased stress, demotivation, and distractions if not implemented thoughtfully. This research aims to evaluate the efficacy of gamified LMS platforms by applying the Push-Pull-Mooring (PPM) Perspective Model. The study seeks to understand the factors that influence students' transition from traditional LMS to gamified systems, including motivations (pull factors), dissatisfactions (push factors), and inhibitors (mooring factors). By systematically reviewing 30 scholarly articles published between 2012 and 2022, the research provides insights into the psychological, behavioral, and educational impacts of gamification within LMS environments. The study aims to identify best practices for designing and implementing gamified LMS that maximize positive outcomes such as intrinsic motivation and active participation while mitigating potential downsides. Furthermore, it explores the implications of gamification for improving educational outcomes and informing future technological innovations in e-learning.